Naldemedine Is Effective in the Treatment of Opioid-Induced Constipation in Chronic Non-Cancer Pain in Subjects With or Without Inadequate Response to Laxatives: 431 - Tack, Jan; Hale, Martin E.; Krauter, Eric; Yamada, Tadaaki; Yokota, Takaaki; Wild, James E. (The American journal of gastroenterology, 2018)
Introduction: Opioid-induced constipation (OIC), a common side effect of opioid utilization in treating chronic non-cancer pain, is caused by the action of opioids on peripheral p-opioid receptors in the enteric nervous system. Naldemedine (NAL), a peripherally acting p-opioid receptor antagonist (PAMORA), demonstrated consistent efficacy and safety in the treatment of OIC from two phase 3, randomised, placebo-controlled, double-blind clinical trials [NCT01965158 (COMPOSE-1) and NCT01993940 (COMPOSE-2)]. In both studies there were significant improvements in the frequency of Spontaneous Bowel Movements (SBMs) and in the OIC symptoms of incomplete evacuation and straining. The effect of NAL in treating the symptoms of OIC in laxative inadequate responders (LIR) has not been reported. Methods: A post-hoc analysis from the pooled two phase 3, randomized, placebo-controlled, doubleblind clinical trials (COMPOSE-1; COMPOSE-2) was performed in the LIR and Non-LIR subgroup. LIR was defined as subjects who were on laxative therapy prior to entering the study and those who stopped its use within 30 days prior to screening, and who signed the informed consent which required the subject to have self-reported OIC (ie, incomplete bowel movement, hard stools, straining, or false alarms). Non-LIR was defined as those subjects who did not receive laxatives or only received rescue laxatives at or after screening. NAL effect on SBM frequency, complete SBMs (CSBM), and SBMs without straining was evaluated. Treatment-emergent adverse events (TEAEs) were defined as those that were reported after randomization and were assessed as well. Results: There was statistically significant increase in SBM frequency (Fig 1), CSBMs (Fig 2), and SBM without straining for both LIR and non-LIR groups as compared to placebo. TEAEs were comparable between the NAL and PBO in both LIR and non-LIR groups. The most common TEAEs were gastrointestinal-related. Conclusion: These data demonstrate that NAL improved the key symptoms of OIC: frequency, incomplete evacuation, and straining, in those subjects who have been previously treated with a laxative. These results suggest that NAL is a useful treatment option in the management of OIC in subjects with chronic non-cancer pain.